Prevalence of Trachoma in Northern Benin: Results from 11 Population-Based Prevalence Surveys Covering 26 Districts. (4th July 2017) - Bio, Amadou Alfa; Boko, Pelagie M.; Dossou, Yannelle A.; Tougoue, Jean-Jacques; Kabore, Achille; Sounouvou, Ignace; Biaou, Jean-Eudes; Nizigama, Lionel; Courtright, Paul; Solomon, Anthony W.; Rotondo, Lisa; Batcho, Wilfrid; et al.
ABSTRACT: Aims : We sought to evaluate trachoma prevalence in all suspected-endemic areas of Benin. Methods : We conducted population-based surveys covering 26 districts grouped into 11 evaluation units (EUs), using a two-stage, systematic and random, cluster sampling design powered at EU level. In each EU, 23 villages were systematically selected with population proportional to size; 30 households were selected from each village using compact segment sampling. In selected households, we examined all consenting residents aged one year or above for trichiasis, trachomatous inflammation – follicular (TF), and trachomatous inflammation – intense. We calculated the EU-level backlog of trichiasis and delineated the ophthalmic workforce in each EU using local interviews and telephone surveys. Results : At EU-level, the TF prevalence in 1–9-year-olds ranged from 1.9 to 24.0%, with four EUs (incorporating eight districts) demonstrating prevalences ≥5%. The prevalence of trichiasis in adults aged 15+ years ranged from 0.1 to 1.9%. In nine EUs (incorporating 19 districts), the trichiasis prevalence in adults was ≥0.2%. An estimated 11, 457 people have trichiasis in an area served by eight ophthalmic clinical officers. Conclusion : In northern Benin, over 8000 people need surgery or other interventions for trichiasis to reach the trichiasis elimination threshold prevalence in each EU, and just over one million people need a combination of antibiotics, facial cleanliness and environmental improvement for the purposes of trachoma's elimination as a public health problem. The current distribution of ophthalmic clinical officers does not match surgical needs.